Penggunaan AC/ID dan Active Learning dalam Pembelajaran Anatomi dalam Large Group - Siti Munawaroh (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2015)
Background: Anatomy is a basic medical science that very important for medical students and other health professions. With a good understanding of the anatomy, they can understand the condition of the patient's illness. However, many of students who complain about the difficulty of anatomy. This paper aims to provide an alternative choice of instructional design in large classes (large group) to improve the quality of learning.Method: literature review.Results: There are many designs of learning that can be applied in a large group. Each has advantages and disadvantages. To improve the quality of student learning, need to be actively involved students in the learning process, so that the material being studied can understand and survive long in the memory of the student.Conclusion: Management of the large group on anatomy lesson is required to produce effective learning. One of the instructional design that can be applied to achieve these objectives is the 4C / ID by applying the principles of active learning.